Challenges in Cytology Specimens With Hürthle Cells - Thodou, Eleni; Canberk, Sule; Schmitt, Fernando (Frontiers in Endocrinology, 2021)
In fine-needle aspirations (FNA) of thyroid, Hurthle cells can be found in a broad spectrum of lesions, ranging from nonneoplastic conditions to aggressive malignant tumours. Recognize them morphologically, frequently represents a challenging for an adequately diagnosis and are associated with a significant interobserver variability. Although the limitations of the morphologic diagnosis still exists, the interpretation of the context where the cells appears and the recent advances in the molecular knowledge of Hurthle cells tumours are contributing for a more precise diagnosis. This review aims to describe the cytology aspects of all Hurthle cells neoplastic and non-neoplastic thyroid lesions, focusing on the differential diagnosis and reporting according to TBSRTC. New entities according to the latest WHO classification are included, as well as an update of the current molecular data.